Correlation between transcutaneous bilirubin levels and total serum bilirubin levels in postnatal period in a tertiary care center - Shonit Kantroo; Girish Shakuntal; Vaibhav K. Gode (International Journal of Contemporary Pediatrics, 2023)
Background: Neonatal jaundice is generally a benign condition seen during the postnatal period. The non-invasive methods including transcutaneous bilirubinometry have been developed for assessment of neonatal jaundice, transcutaneous bilirubin TcB) meters noninvasively estimate the bilirubin levels by measuring light transmission through the skin of neonates this value is then to be plotted against a chart in order to look for hyperbilirubinemia. Aim was to determine the efficacy of measuring the transcutaneous bilirubin as a screening tool for clinically significant hyperbilirubinemia. Methods: Study was a cross sectional study conducted under pediatric department of SMBT IMS and RC at tertiary care center after taking the approval from the ethical committee. Total of 110 neonates that appear to be clinically suffering from neonatal jaundice were considered for study after consent from respective parent/ guardian. Neonatal TCB levels and serum bilirubin levels were done. If bilirubin levels lie in phototherapy range, then baby was shifted to NICU and phototherapy treatment was given, and once levels came within normal range after the phototherapy treatment, again serum bilirubin levels were measured in order to compare pre-and post-treatment levels. Results: Present study showed male preponderance. 64 were male and 46 were female. Majority 61% were full term normal delivery and 39% were LSCS. Mean TCB level was 8.5±2.8. Statistical significance was seen for TCB and sever hyperbilirubinemia. Conclusions: Present study concluded that hyperbilirubinemia is commonly seen among males. Newborn delivered had hyperbilirubinemia. Statistical significance was seen between TCB level and severity of the disease. Thus, neonatal TCB levels can be used as a screening test for detecting hyperbilirubinemia in neonates. As TCB is a noninvasive and cost effective it can be used widely as predictor of the disease.